An Exploration of EFL Teachers’ Challenges and Strategies during the Pandemic: A Case of Emergency Blended Synchronous Education - Kanık, Mehmet; Hadizadeh, Abbas (UIN Salatiga, 2022)
With the lockdowns caused by the COVID-19 pandemic, educational institutions had to make swift educational decisions such as emergency blended synchronous education without thoroughly scrutinizing its effects. This study explores the experiences of a group of seven EFL teachers of a blended learning model during the pandemic in Northern Cyprus higher education. The study adopted a qualitative design by interviewing seven teachers on their experiences during the pandemic, particularly focusing on a blended instructional mode of education over the fall academic semester in 2020. The study results reveal that the study participants employed various strategies to cope with the challenges ascribed to the blended mode of delivery. The study's findings offer some implications for second language teachers and the use of technology in second language education. Keywords: EFL teachers, challenges, emergency blended synchronous education, blended education